Release of interleukin-10 and neurotrophic factors in the choroid plexus: possible inductors of neurogenesis following copolymer-1 immunization after cerebral ischemia - Cruz, Yolanda (Neural Regen Res, 2018)
Copolymer-1 (Cop-1) is a peptide with immunomodulatory properties, approved by the Food and Drug Administration of United States in the treatment of multiple sclerosis. Cop-1 has been shown to exert neuroprotective effects and induce neurogenesis in cerebral ischemia models. Nevertheless, the mechanism involved in the neurogenic action of this compound remains unknown. The choroid plexus (CP) is a network of cells that constitute the interphase between the immune and central nervous systems, with the ability to mediate neurogenesis through the release of cytokines and growth factors. Therefore, the CP could play a role in Cop-1-induced neurogenesis. In order to determine the participation of the CP in the induction of neurogenesis after Cop-1 immunization, we evaluated the gene expression of various growth factors (brain-derived neurotrophic factor, insulin-like growth factor 1, neurotrophin-3) and cytokines (tumor necrosis factor alpha, interferon-gamma, interleukin-4 (IL-4), IL-10 and IL-17), in the CP at 14 days after ischemia. Furthermore, we analyzed the correlation between the expression of these genes and neurogenesis. Our results showed that Cop-1 was capable of stimulating an upregulation in the expression of the genes encoding for brain-derived neurotrophic factor, insulin-like growth factor 1, neurotrophin-3 and IL-10 in the CP, which correlated with an increase in neurogenesis in the subventricular and subgranular zone. As well, we observed a downregulation of IL-17 gene expression. This study demonstrates the effect of Cop-1 on the expression of growth factors and IL-10 in the CP, in the same way, presents a possible mechanism involved in the neurogenic effect of Cop-1.